AJARAN PEMBEBASAN DALAM TEKS MANTRIKOPANIṢAD - Gede Endy Kumara Gupta (Pangkaja: Jurnal Agama Hindu, 2023)
The Mantrikopaniṣad is one of the Upaniṣad that is part of the Śukla Yajur Veda. It consists of only 20 śloka, but the content of the text contains so many seeds of teachings that further developed into important thought and discipline for Hindus. The seeds of these teachings include the teachings on the reality of Ātman and Brahman, the concept of God who is Saguṇa and Nirguṇa, the concept of Māyā, the philosophy of Divinity (Advaita and Dvaita Vedānta), the teachings of tattva-Sāṁkhya, and also the teachings on union with Brahman. Of all the śloka given in the Mantrikopaniṣad, the text basically attempts to convey a teaching related to the liberation (Mokṣa) which is attained through certain paths and methods, which are Bhakti, Jnāna (knowledge), and Karma (action). For this reason, the research specifically attempts to analyze how the form of the teaching of liberation (Mokṣa) is contained in the Mantrikopaniṣad.